JUSTIFIKASI KEBUTUHAN PERUBAHAN LAHAN SAWAH YANG DILINDUNGI BAGI PENGEMBANGAN SEKTOR UNGGULAN DI KOTA PEKALONGAN - Sutoto Sutoto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
Based on the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency number 1589/SK-HK.02.01/XII/2021, there are 254.17 hectares of protected paddy fields that are allocated for other land uses in the Spatial Plans of Pekalongan City. The implication will hamper the process of space utilization. This article is intended to identify the leading sectors. The development of leading sectors is the basis for policies to utilize protected paddy fields for other land uses in Pekalongan City. The method used is Klassen Typology analysis, Location Quotient analysis and Shift-Share analysis. The results of the analysis show that the trade and services sector is one of the leading sectors. Trade and services are one of the urban activities that utilize the protected paddy fields. Keywords: Protected paddy fields, spatial plans, land use, leading sectors